Theoretical modelling of momentum transfer function of bi-disperse porous media - Hooman, K.; Sauret, E.; Dahari, M. (2015)
The aim of this paper is to obtain the momentum transfer coefficient between the two phases, denoted by f and p, occupying a bi-disperse porous medium by mapping the available experimental data to the theoretical model proposed by Nield and Kuznetsov 1. Data pertinent to plate-fin heat exchangers, as bi-disperse porous media, were used. The measured pressure drops for such heat exchangers are then used to give the overall permeability which is linked to the porosity and permeability of each phase as well as the interfacial momentum transfer coefficient between the two phases. Accordingly, numerical values are obtained for the momentum transfer coefficient for three different fin spacing values considered in the heat exchanger experiments. (C) 2014 Elsevier Ltd. All rights reserved.